Hypolipidemic Effects of Three Purgative Decoctions. (14th February 2011) - Tseng, Sung-Hui; Chien, Ting-Yi; Chen, Jiun-Rong; Lin, I-Hsin; Wang, Ching-Chiung
Abstract : In traditional Chinese medicine (TCM), purgation is indicated when a person suffers an illness due to the accumulation of evil internal heat. Obese individuals with a large belly, red face, thick and yellow tongue fur, constipation, and avoidance of heat are thought accumulates of evil internal heat, and they are also treated with purgatives such as Ta-Cheng-Chi-Tang (TCCT), Xiao-Chen-Chi-Tang (XCCT), and Tiao-Wei-Chen-Chi-Tang (TWCCT) by TCM doctors. In previous studies, our group found that TCCT has potent anti-inflammatory activity, and that XCCT is an effective antioxidant. Since rhubarb is the principle herb in these three prescriptions, we will first present a thorough review of the literature on the demonstrated effect (or lack of effect) of rhubarb and rhubarb-containing polyherbal preparations on lipid and weight control. We will then continue our research with an investigation of the anti-obesity and lipid-lowering effect of TCCT, XCCT, TWCCT, and rhubarb extracts using two animal models. TWCCT lowered the serum triglyceride concentration as much as fenofibrate in Triton WR-1339-treated mice. Daily supplementation with XCCT and TWCCT significantly attenuated the high-fat-diet-induced hypercholesterolemia in rats. In addition, TWCCT also significantly lowered the high-fat-diet-induced hypertriglycemia. Although feeding high-fat diet rats with these extracts did not cause loose stools or diarrhea or other deleterious effects on renal or hepatic function. None of these extracts lowered the body weight of rats fed on high-fat diet. In conclusion, the results suggest that XCCT and TWCCT might exert beneficial effects in the treatment of hyperlipidemia.